An Efficient Provable Forward Secure Blind Signature Scheme for Cryptocurrency - Mariusz JURKIEWICZ (Communications of International Proceedings, 2021)
In this paper we construct and perform an in-depth analysis of a forward-secure blind signature scheme, which can be used in some protocols associated with cryptocurrency. The construction is based on both properties of bilinearity and certain relations between nodes of binary trees, where a number of leaves is the same as a number of time periods in the scheme. The bilinearity is induced by Type 3 pairing defined over a product of two cyclic groups of the same order, and with values in a third cyclic group. The security proof of the scheme is conducted in the random oracle model and is being reduced to the hardness of solving a certain kind of the Weak -th Bilinear Diffie-Hellman Inversion problem that we denote by .
Keywords: Forward Security; Blindness; Random-Oracle Model; Bilinear DH Inversion Problem